Two-Year’ Experience with diaphragmatic injuries at Aboslim Trauma Hospital, Tripoli-Libya (2021-2023) (مجلة العلوم الشاملة, 2025)
BackgroundTraumatic diaphragmatic injuries (TDI) are uncommon but potentially life-threatening, typically resulting from high-energy blunt or penetrating trauma. Due to their often subtle presentation and association with other injuries, TDIs are frequently missed during initial evaluation. Delayed diagnosis can result in herniation of abdominal organs into the thoracic cavity, respiratory compromise, and increased morbidity. This study reviews our institutional experience in diagnosing and managing TDIs over a two-year period at Abo-Slim Trauma Hospital, Tripoli, Libya.Methods: We conducted a retrospective review of all patients diagnosed with diaphragmatic injuries between June 2021 and June 2023. Data included demographics, mechanism and side of injury, timing and modality of diagnosis, surgical approach, and outcomes. Surgical techniques included laparotomy, laparoscopy, and thoracotomy. Patients were coded DI-2021-7-01 to DI-2021-7-08.Results: Eight patients were identified, aged (35.9±13.6, Mean±STDVV). Injuries involved the left diaphragm in 7 cases (87.5%) and the right in 1 case (12.5%). Mechanisms included road traffic accidents(n=5),stab wounds(n=2),,and one fall. Diagnosis was immediate in 5 cases (62.5%) and delayed in 3 (37.5%).Surgical repair was performed via laparotomy in 5 cases (indicated by peritonitis or positive FAST), laparoscopy in 2 stable patients, and thoracotomy in one delayed diagnosis.Conclusion: TDIs remain challenging to diagnose, especially when associated with multiple injuries.   The left side is more frequently affected, likely due to the protective role of the liver on the right. Missed injuries contribute to increased complications and length of stay. Early surgical exploration, particularly using laparoscopy in stable patients, improves detection and outcomes. High clinical suspicion and vigilant trauma assessment are critical in ensuring timely intervention.